2020
DOI: 10.1093/ndt/gfaa350
|View full text |Cite
|
Sign up to set email alerts
|

Tissue sodium stores in peritoneal dialysis and hemodialysis patients determined by sodium-23 magnetic resonance imaging

Abstract: Background Tissue sodium content in patients on maintenance hemodialysis (MHD) and peritoneal dialysis (PD) were previously explored using 23Sodium magnetic resonance imaging (23NaMRI). Larger studies would provide a better understanding of sodium stores in patients on dialysis as well as the factors influencing this sodium accumulation. Methods In this cross-sectional study, we quantified the calf muscle and skin sodium cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Previous 23 Na-MRI investigations revealed a gender-dependence and age-correlation of tissue Na + storage. 7,10 Indeed, we have also found these correlations in our cohort pre and post transplantation. Furthermore, 2 out of 31 CKD patients were diagnosed with type 2 diabetes mellitus, a condition known to enhance tissue Na + accumulation in HD patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Previous 23 Na-MRI investigations revealed a gender-dependence and age-correlation of tissue Na + storage. 7,10 Indeed, we have also found these correlations in our cohort pre and post transplantation. Furthermore, 2 out of 31 CKD patients were diagnosed with type 2 diabetes mellitus, a condition known to enhance tissue Na + accumulation in HD patients.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, results should not be generalized to all ethnicities, which is important as for instance African Americans are known to accumulate higher amounts of tissue Na + . 10 The pathophysiological implications of tissue Na + storage have to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary observations from our group point out that children may have the lowest tissue sodium concentration [ 66 •], as opposed to adult dialysis patients where tissue sodium concentrations are largest [ 67 , 68 ]. Though intuitively increased dietary sodium intake should be associated with increased tissue sodium levels, clinical evidence in this respect is scarce; Bracconier et al have shown that in healthy individuals, higher salt intake is associated with higher sodium concentrations in muscle tissue and sweat [ 69 •].…”
Section: Sodium-23 Magnetic Resonance Imaging and Chronic Kidney Diseasementioning
confidence: 99%
“…Studies visualising the sodium tissue signal with 23 Na MRI have demonstrated that tissue sodium is correlated with age [ 24 , 59 , 71 73 ] and male gender [ 24 , 71 74 ] in healthy controls as well as those with CKD. In CKD, tissue sodium concentrations increase progressively across the spectrum [ 74 ].…”
Section: Main Textmentioning
confidence: 99%